2020
DOI: 10.1126/sciadv.abc6721
|View full text |Cite
|
Sign up to set email alerts
|

Disparate compound eyes of Cambrian radiodonts reveal their developmental growth mode and diverse visual ecology

Abstract: Radiodonts are nektonic stem-group euarthropods that played various trophic roles in Paleozoic marine ecosystems, but information on their vision is limited. Optical details exist only in one species from the Cambrian Emu Bay Shale of Australia, here assigned to Anomalocaris aff. canadensis. We identify another type of radiodont compound eye from this deposit, belonging to ‘Anomalocaris’ briggsi. This ≤4-cm sessile eye has >13,000 lenses and a dorsally oriented acute zone. In both taxa, lenses were added ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 61 publications
2
26
0
Order By: Relevance
“…For instance, the neural architectures seen in Cambrian panarthropods (Ma et al 2012; Tanaka et al 2013; Cong et al 2014; Strausfeld 2015) are quite conserved and similar in complexity to those in the present. Likewise, Ma et al (2012: p. 258) characterize compound eyes in the Cambrian as being “in size and resolution, equal to those of modern insects and malacostracans.” Such inference about Cambrian compound eyes is seen, for instance, from Paterson et al's (2011, 2020) finding that the stem-arthropod Anomalocaris compared well to most living arthropods in eye size, high ommatidial lens count per eye, and low interommatidial angles, all factors that correlate with visual acuity in the present. These claims would imply that modern levels of cognition and sensory acuity were achieved exceptionally early for arthropods.…”
Section: Discussionsupporting
confidence: 64%
“…For instance, the neural architectures seen in Cambrian panarthropods (Ma et al 2012; Tanaka et al 2013; Cong et al 2014; Strausfeld 2015) are quite conserved and similar in complexity to those in the present. Likewise, Ma et al (2012: p. 258) characterize compound eyes in the Cambrian as being “in size and resolution, equal to those of modern insects and malacostracans.” Such inference about Cambrian compound eyes is seen, for instance, from Paterson et al's (2011, 2020) finding that the stem-arthropod Anomalocaris compared well to most living arthropods in eye size, high ommatidial lens count per eye, and low interommatidial angles, all factors that correlate with visual acuity in the present. These claims would imply that modern levels of cognition and sensory acuity were achieved exceptionally early for arthropods.…”
Section: Discussionsupporting
confidence: 64%
“…Indeed, in hemimetabolous insects, compound eyes grow by adding new units peripherally rather than between units that have already formed (Friedrich, 2008). Even in fossil radiodonts, compound eye units were added at the periphery (Paterson et al, 2020). Finally, consistent with these expectations, it was recently demonstrated that the eyes of tiny juvenile jumping spiders have approximately the same number of PRs as those of their much larger adult counterparts (Goté et al, 2019).…”
Section: The Apoptosis Rate Of Remaining Cells Molds the Final Eye La...mentioning
confidence: 75%
“…Another important trait associated with the appearance of radiodontans is the presence of well‐developed compound eyes, which in these taxa are stalked (Paterson et al ., 2011; but see Paterson, Edgecombe & García‐Bellido, 2020), whereas lobopodians only possess simple ocelli (Ma et al ., 2012a), when present (Fig. 2).…”
Section: Assembly Of the Arthropod Body Planmentioning
confidence: 99%